Slow growth and delayed maturation in a Critically Endangered insular flying fox (Pteropus natalis) - Todd, Christopher M (J Mammal, 2018)
Flying foxes (family Pteropodidae) have distinct life histories given their size, characterized by longevity, low reproductive output, and long gestation. However, they tend to decouple the age at which sexual maturity is reached from the age at which they reach adult dimensions. We examined growth, maturation, and reproduction in the Critically Endangered Christmas Island flying fox (Pteropus natalis) to determine the timing of sex-specific life cycle events and patterns of growth. We estimated that juvenile growth in forearm length and body mass increased at a mean rate of 0.029 ± 0.005 mm/day and 0.33 ± 0.07 g/day for both males and females alike. Using these growth rates, we determined that the birth of pups occurs between December and March, with young becoming volant between June and August. The age at maturation for P. natalis is one of the oldest among all bat species. Juvenile males began to mature 15 months after birth and reached maturity 27 months after birth. Females reached maturity 24 months after birth at a significantly smaller body mass (3.6%) and forearm length (1.4%) than males. Significant sexual dimorphism and bimaturation was observed, with juvenile males being 1.5% and adult males being 1.9% larger on average than females for skeletal dimensions only. Growth and maturation are even slower in P. natalis than in the few other Pteropus species studied to date. The slow growth and delayed maturation of P. natalis imply slower potential population growth rates, further complicating the recovery of this Critically Endangered single-island endemic.